2017
DOI: 10.1016/j.jbiomech.2017.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast-like synoviocyte mechanosensitivity to fluid shear is modulated by interleukin-1α

Abstract: Fibroblast-like synoviocytes (FLS) reside in the synovial membrane of diarthrodial joints and are exposed to a dynamic fluid environment that presents both physical and chemical stimuli. The ability of FLS to sense and respond to these stimuli plays a key role in their normal function, and is implicated in the alterations to function that occur in osteoarthritis (OA). The present work characterizes the response of FLS to fluid flow-induced shear stress via real-time calcium imaging, and tests the hypothesis th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 39 publications
(49 reference statements)
1
32
0
Order By: Relevance
“…Mechanical stress has been reported to be involved in the control of synovitis. Estell reported that fibroblast-like synovial cells on the synovial surface express IL-1α in response to shear stress [ 21 ]. Zhang reported that the expression of MMPs and lysyl oxidases (LOX) in synovial fibroblasts varied depending on the intensity of the applied mechanical stress [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical stress has been reported to be involved in the control of synovitis. Estell reported that fibroblast-like synovial cells on the synovial surface express IL-1α in response to shear stress [ 21 ]. Zhang reported that the expression of MMPs and lysyl oxidases (LOX) in synovial fibroblasts varied depending on the intensity of the applied mechanical stress [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Directly transmitted forces are closely associated with pressure-induced bone resorption; indirect forces may work via inflammatory processes [130] and modulation of osteoclastogenesis [131]. Innate immune cells [130], fibroblasts [132], osteocytes [115] and other cells can sense mechanical stimuli and respond to physiological and non-physiological forces or pressures.…”
Section: Mechanical Osteolysis and Synergies With Inflammatory Agentsmentioning
confidence: 99%
“…This cascade of events depends on the level of mechanical forces applied to the joint (light, moderate, or high). The ability of Type B synoviocytes to adapt and respond to these stimuli is essential in both normal and OA joints . When type B synoviocytes are activativated (invade cartilage and destroy it) secondary to inflamed synovium that is often present in OA, pro‐inflammatory cytokines such as IL‐1β, TNF‐α, and IL‐6 are released causing chondrocyte activity to produce degradative enzymes (collagenase, neutral proteinases, and cathepsins) which actively invade the joint space reducing tissue repair and regeneration …”
Section: Biomarkers In Osteoarthritismentioning
confidence: 99%